Effect of pregnancy in 42 elite to world-class runners on training and performance outcomes - Darroch, F.; Schneeberg, A.; Brodie, R.; Ferraro, Z. M.; Wykes, D.; Hira, S.; Giles, A. R.; Adamo, K. B.; Stellingwerff, T. (Medicine & Science in Sports & Exercise, 2023)
Purpose: The International Olympic Committee expert group on pregnancy has identified a paucity of information regarding training and performance in truly elite athletes. Thus, the purpose of this study was to quantify elite runners` training volume throughout pregnancy and postpartum competition performance outcomes. Methods: Forty-two elite (>50% competed at the World Championships/Olympic) middle-/long-distance runners` training before, during, and after pregnancy (quality/quantity/type) data (retrospective questionnaire) and competition data (published online) were collected. Results: Running volume decreased significantly (P < 0.01) from the first trimester (63 ± 34 km·wk-1) to the third trimester (30 ± 30 km·wk-1). Participants returned to activity/exercise at ~6 wk postpartum and to 80% of prepregnancy training volumes by 3 months. Participants who intended to return to equivalent performance levels postpregnancy, there was no statistical decrease in performance in the 1 to 3 yr postpregnancy compared with prepregnancy, and ~56% improved performances postpregnancy. Conclusions: This study features the largest cohort of elite runners training and competition outcomes assessed throughout pregnancy, with training volumes being approximately two to four times greater than current guidelines. For the first time, performance was directly assessed (due to the quantifiable nature of elite running), and study participants who intended to return to high-level competition did so at a statistically similar level of performance in the 1- to 3-yr period postpregnancy. Taken together, this article provides much needed insights into current training practices and performance of elite pregnant runners, which should help to inform future training guidelines as well as sport policy and sponsor expectations around return to training timelines and performance.